Measurement Of Basketball Physical Tests On Students Of SMP Negeri 1 Indralaya Using Outdoor Laboratory In Educational Park (Journal of Physical Education Health and Sport, 2023)
This study aims to determine the physical tests of the basketball players at SMP Negeri 1 Indralaya. This research is a quantitative research with a descriptive design. The subjects of this study were basketball players at SMP Negeri 1 Indralaya with a total of 30 players consisting of 16 boys and 14 girls. In this study to determine endurance using the 1000 meter running test for men and 800 meters for women, speed using the 50 meter running test, explosive power of leg muscles using the upright jump test, arm muscle strength using the hanging body lift test for men and hanging elbows. for women, abdominal muscle strength used the lying down test, agility used the Illinois agility run test and flexibility used the sit and reach test. The data analysis technique uses descriptive percentages. The results obtained from the study of physical test measurements of basketball players at SMP Negeri 1 Indralaya were 2 players (7%) in the good category, 25 players (83%) in the medium category, 3 players (10%) in the less category, while there were no soccer players. basketball at SMP Negeri 1 Indralaya in very good and very poor categories. It can be concluded that the average physical test for basketball players at SMP Negeri 1 Indralaya is in the moderate category.